The Effect Of Green Information Systems On Energy Efficiency And Low Carbon Footprint: Mediating Effects Of Green Supply Chain Integration - Teoh, Tek Woei (2015)
The Industrial Revolution altered the society and also the relationship with the environment and the society, increasing the natural resources consumption such as the fossil fuels in order to meet the pace of development of new products introduction. This has created harmful products from the manufacturing process such as excess carbon emission, pollution and also depletion of the natural resources which lead to increase energy prices globally. Lately, concern and focus for the environment has motivated the manufacturing industry to lead a proactive role towards greener manufacturing practices and towards more environments sustainable. With all the issues and challenges facing toward environment sustainability, there was a need to raise the awareness of the important role of information systems and supply chain integration in leading towards better environmental performances among all the manufacturing firms in Malaysia. This study thus carried out to further extend the research model of green information systems and green supply chain integration implementation impact towards energy efficiency and low carbon footprint of firms in Malaysia. An online survey is administered to manufacturing industry in Malaysia. Total 159 data were analyzed using the structural equation modeling with Smart PLS 3.0. Analytical results demonstrated that green information systems and green supply chain integration play a crucial role towards better energy efficiency and low carbon footprint. This study presents the practical implication for practitioners which underlined a need to greening their supply chain integration and information systems.